(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
The study of the philosophy of Thomas Hobbes as a paradigm of modernity leads the author to discuss the concept of modernity. If by modernity we understand modern times, it is worthwhile asking some questions regarding the history of modern thought. For example, is modernity one thing, so that it is possible to treat it systematically, taking it as a whole? If not, if there are a number of modernities, as would seem to be the case, is hobbs representative of any of them, of all of them or possibly of none? To attempt to answer this questions, it is not only important to understand the Hobbes’ philosophy and its place in history, but also to reflect on our own conception of modernity.